From the Margins of the Colophon: Arab Orthodox Monasticism in Ruins - Eldridge, Aaron Frederick (Exchange, 2020)
Abstract This article, drawn from two years of ethnographic fieldwork, traces the temporal articulations of Orthodox Christian monasticism in post-war Lebanon. It recounts one Lebanese monastery’s reinhabitation—founded on the uncanny return of its martyred saints—as evidence of monastic life’s constitutive intimacy with ruination. The article subsequently explores the grammars of temporal delimitation (the juridical and territorial apparatuses of state land tenure as well as the archival trace of historiography) and argues that these approaches disable the possibility of accounting for such a return in ruins. Offering the Orthodox tradition’s language of ascetical dispossession as an analytic counterpoint, the article takes up the monastic language of renunciatory withdrawal. The temporality of this withdrawal, in its protological and its eschatological marginalization, brings into relief a form of time that presses upon the limits of historiography.